2018
DOI: 10.1016/j.anifeedsci.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Performance and meat quality of Nellore bulls fed crude glycerin combined with soybean oil

Abstract: The objective of this experiment was to determine the effect of crude glycerin combined with soybean oil on the performance and fatty acid composition of the longissimus muscle in Nellore bulls. Twenty-eight Nellore young bulls, each with an initial body weight (BW) of 408 ± 29 kg (age 20 ± 2 months), were used in a completely randomized design over a period of 84 days in a 2 × 2 factorial arrangement. The treatments were diets with crude glycerin at 100 g/kg DM (CG+) or without crude glycerin (CG−); diet with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…It is consistent with others that did not find any differences in cooking loss by dietary lipid source supplementation, not only in Malpura lambs (Bhatt et al 2020) but also in Nellore bulls (Fiorentini et al 2018). Sanudo et al (2000) clarified that lower shear force values were related to the higher fat diets fed to lambs.…”
Section: Meat Fatty Acid Compositionsupporting
confidence: 91%
“…It is consistent with others that did not find any differences in cooking loss by dietary lipid source supplementation, not only in Malpura lambs (Bhatt et al 2020) but also in Nellore bulls (Fiorentini et al 2018). Sanudo et al (2000) clarified that lower shear force values were related to the higher fat diets fed to lambs.…”
Section: Meat Fatty Acid Compositionsupporting
confidence: 91%
“…No significant difference was observed in the pH after day 1 throughout the period of aging. The ultimate pH values observed for the muscles were within the normal range (5.4–5.8) for beef (Fiorentini et al, ). Similar results were observed by Shange, Makasi, Gouws, and Hoffman () who also observed a similar decline in the pH of Biceps femoris aged for 12 days at refrigeration temperature.…”
Section: Resultsmentioning
confidence: 64%
“…According to another hypothesis, CG increases the energy density in the diet by inducing a chemical feeling of satiety, and eventually, DMI is suppressed (Saleem and Singer, 2018). Fiorentini et al (2018) stated that the DMI decrease might be related to the decrease in the taste of the diet due to the presence of impurities such as methanol in CG.…”
Section: Effect Of Crude Glycerin On Dry Matter Intake and Performancementioning
confidence: 99%
“…Borghi et al (2016) added 0, 10, and 20% CG to lamb diets, and they did not observe any significant changes in other fatty acids, except for an increase in margaric acid percentage in TFAs in meat. Fiorentini et al (2018) supplemented beef cattle diets with soybean oil and CG. They found that animals given soybean oil incorporated 32% more linoleic acids and 40% more conjugated linoleic acids into their muscles than those given CG.…”
Section: Effect Of Crude Glycerin On Meat Fatty Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation